The Influence of Work Motivation, Organizational Culture and Work Discipline on Employee Performance Through Job Satisfaction as Intervening Variables at BPJS Ketenagakerjaan throughout DKI Jakarta Region - Junaedi, Muhammad Azis; Digdowiseiso, Kumba (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
Rewards and motivation are one of the most important instruments in employee performance. Other variables are also included in a study to determine the positive or negative effect of a level of employee satisfaction, where these factors affect the performance of employees working in a company. While the factors that affect job satisfaction can come from the individual itself, social factors, the main job faced and also external factors. Another problem faced by companies in general is the difficulty in measuring the factors that affect employee performance. So, through the questionnaire variables in the form of work motivation, organizational culture and work discipline, measurements are carried out by processing data using the SEM method so that the intervention value will be published as a satisfaction level value that affects employee performance level values. The data collection method used in this study was by using a questionnaire method which was distributed to 300 respondents, namely BPJS Employment employees in the entire DKI Jakarta area. With the results of calculating the average descriptive analysis of the 3 dependent variables, namely work motivation variable 4.79, organizational culture variable 4.93 and work discipline variable 4.86. While the results of the analysis of employee performance variables were 4.94 and the results of the analysis of job satisfaction variables were 4.75. So, it means that motivation, organizational culture and work discipline have a positive effect on job satisfaction and performance.